Self-regulation and resilience: the role on active procrastination of young adults - Vincent, Ivy Josiah; Law, Mei-Yui; Chew, Zariv Long-Kwan; Lai, Chooi-Seong (International Journal of Public Health Science (IJPHS), 2024)
Our current dynamic digital era has generated active procrastination which is a popular trend of behaviour among young adults. Deciphering this reckless habit reveals a fascinating truth in which active procrastination thrives on strategic planning for task completion. This study examined i) self-regulation and resilience as the significant predictors of active procrastination among young adults, ii) the significant difference in active procrastination among university students and working young adults, iii) significant gender differences among university students, and iv) among working young adults. A total of 192 respondents completed the questionnaires, Self-Regulation Scale, Connor-Davidson Resilience Scale, and Active Procrastination Scale. Through quantile regression, results show that self-regulation is a significant predictor of active procrastination among young adults. Independent t-tests shows there is no significant differences in active procrastination among university students and working young adults. However, there are significant gender differences in active procrastination among university students, but not among working young adults. These findings indicate that self-regulation plays a significant role in cultivating active procrastinating among young adults. Furthermore, interesting findings are discovered for gender differences as males have relatively higher active procrastination scores. Hence, the findings emphasize the need for workshops to transform young adults to become active procrastinators through enhancing self-regulation.